2007
DOI: 10.1248/yakushi.127.1723
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Paracetamol and Orphenadrine Citrate in Pharmaceutical Tablets by Modeling of Spectrophotometric Data Using Partial Least-Squares and Artificial Neural Networks

Abstract: The estimation of paracetamol and orphenadrine citrate in a multicomponent pharmaceutical dosage form by spectrophotometric method has been reported. Because of highly interference in the spectra and the presence of non-linearity caused by the analyte concentrations which deviate from Beer and Lambert's law, partial least-squares (PLS) and artiˆ-cial neural networks (ANN) techniques were used for the calibration. A validation set of spiked samples was employed for testing the accuracy and precision of the meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Several studies in the literature have reported analytical methods for the simultaneous determination of PAR and COD , as well for PAR and TRA . On a smaller scale, some other studies in the literature have reported methods for simultaneous determination of PAR and ORP . However, for the simultaneous determination of PAR and PRO only one work has been reported , and for PAR and SCO, to the best of our knowledge, no previous work has reported this possibility.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Several studies in the literature have reported analytical methods for the simultaneous determination of PAR and COD , as well for PAR and TRA . On a smaller scale, some other studies in the literature have reported methods for simultaneous determination of PAR and ORP . However, for the simultaneous determination of PAR and PRO only one work has been reported , and for PAR and SCO, to the best of our knowledge, no previous work has reported this possibility.…”
Section: Introductionmentioning
confidence: 95%
“…Von Mering first introduced PAR as an antipyretic/analgesic drug in 1893 , as a substitute for aspirin because it does not cause problems in patients who are prone to gastric issues. PAR is frequently found in association with other pharmaceuticals in the same formulation due to the synergic analgesic or supra additive effect of this combination, superior to each drug individually . PAR can be combined with orphenadrine (ORP), for the relief of muscle pain and in tension headaches ; with tramadol (TRA) to increase analgesia and reduce adverse events ; with codeine (COD) to treat acute pain and pyrexia ; with promethazine (PRO) as an antipyretic and antiemetic ; and with scopolamine (SCO) in therapy for gastrointestinal disorders such as colic .…”
Section: Introductionmentioning
confidence: 99%
“…However, this technique could not be applied without a special program like Matlab®. It is anticipated that the spectro-chemometric methods can provide a fast-quantitative study of the pharmaceutical dosage forms [10][11][12][13][14].…”
Section: Sachetsmentioning
confidence: 99%
“…The literature revealed that several methods have been carried out for the analysis of PAR and ORP in their mixture form or in their combination with other drugs. PAR & ORP were determined by spectrophotometric methods, HPLC methods, TLC and microemulsion HPLC method and square wave voltammetric method [1,[3][4][5][6][7][8][9][10][11][12][13]. To the best of our knowledge, there is no reported method for the determination of this drug mixture using Isoabsorptive point technique.…”
Section: Introductionmentioning
confidence: 99%